Learning Mathematics By Discovery - Prasad, Kripa Sindhu (Academic Voices: A Multidisciplinary Journal, 2011)
Discovery learning can be effectively used to stimulate and maintain interest in mathematics. Furthermore, such an approach promotes creativity and originality in students which are important for a student’s future success in mathematics. This paper highlights and illustrates learning by discovery. Keywords Pure discovery, guided discovery, exploration, verification, generalization DOI: http://dx.doi.org/10.3126/av.v1i0.5307 Academic Voices 2011; 1: 31-33